Evaluasi dan Perbaikan User Experience Website E-Learning SMK Negeri 2 Malang menggunakan Teknik TUXEL 2.0 dan Pendekatan Human-Centered Design - Riyan Bagaskara; Buce Trias Hanggara; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Online learning that has been applied in Indonesia since the COVID-19 pandemic has made schools need to prepare facilities for the learning activity. SMK Negeri 2 Malang uses web-based and mobile application-based e-learning. It is known as MClass. However, interviews with several students of SMK Negeri 2 Malang showed that there were some obstacles in using the MClass, such as a complicated website display, no help or instructions on using the website, etc. This study aims to evaluate and design the user experience solution design of the e-learning website of SMK Negeri 2 Malang using the TUXEL 2.0 technique and the Human-centered Design approach. The Human-centered Design begins with analyzing the context of use, analyzing user needs, designing solution designs, and evaluating solution designs. The user needs analysis stage and the solution design evaluation stage use the TUXEL 2.0 technique. Based on the evaluation, it is known that in the initial evaluation there were a total of fifty problem items, while in the evaluation of the solution design there were a total of eight problem items. In the initial evaluation it was found that there were eight items that were categorized as â€œbadâ€ and only one item that was categorized as â€œvery goodâ€, but in the evaluation of the solution design there were ten items that were categorized as â€œvery goodâ€ and two items that were categorized as â€œgoodâ€.